Impact of growth parameters on refraction and ocular biometry in Chinese preschool children (3–6 years): the Beijing children eye study - Wang, Chao; Yuan, Jing; Xu, Qing; Jiang, Aimin (Frontiers in Pediatrics, 2025)
BackgroundThis study aims to investigate the relationship between growth and ocular biometry/refraction in preschool children aged 3–6 years.MethodsThis study performed a retrospective evaluation utilizing anonymized data from a pre-existing cohort of children aged 3–6 years, who were recruited from 11 kindergartens in the Shunyi District of Beijing. Out of the 1,144 children assessed, a total of 1,021 (89.2%) were included in the final analysis. The gathered data adhered to ethical guidelines suitable for subsequent analysis. Information on sex, age, stature, mass, and body mass index (BMI) served as indicators of growth and developmental stages. Ocular measurements such as axial length (AL) and anterior chamber depth (ACD) were obtained using the Lenstar LS900 device. Cycloplegic refraction and corneal curvature were assessed with an autorefractor. The correlation between growth metrics and ocular parameters, including refraction, was examined. To determine statistical significance, regression analyses were carried out.ResultsAfter making adjustments for age, sex, and weight, every 1-cm increment in height corresponded to a 0.017 mm rise in AL and a 0.005 mm increase in ACD. Regarding weight, following adjustments for age, sex, and height, each 1-kg increase was linked to a 0.017 mm augmentation in AL and a 0.006 mm rise in corneal curvature. Comparable significant correlations were also noted with BMI.ConclusionHigher child height is correlated with longer AL, deeper anterior chamber, and flatter cornea. Weight and BMI show similar associations with AL and corneal curvature radius.